Occurrence of Pesticide Residues in Spanish Honey Measured by QuEChERS Method Followed by Liquid and Gas Chromatography–Tandem Mass Spectrometry - Roberto Jesús Lasheras; Regina Lázaro; Juan Carlos Burillo; Susana Bayarri (Foods, 2021)
In the current study, the QuEChERS extraction method with slight modifications, followed by liquid and gas chromatography–tandem mass spectrometry, was applied for the determination of 399 pesticide residues in 91 raw honey samples from northeastern Spain. The quality control procedure established in Document No. SANTE/12682/2019 was successfully followed: the responses in reagent blank and blank honey samples were below 30% of the reporting limit (0.01 mg kg−1) for all analysed compounds, the correlation coefficients (R2) were higher than 0.99 in most calibration curves, the deviation of back-calculated concentration from the true concentration was below ±20% (using the standard of 50 μg L−1 concentration), and the recoveries of spiked samples on matrix were within the range of 70–120% for almost all analytes. Only chlorfenvinphos (2–7.8 ng/g) and coumaphos (8.8–37 ng/g) were detected in 13 samples, and neither were observed to exceed their maximum residue limits (MRLs). Dietary risk assessment for pesticide residues in honey above their lowest calibrated level (LCL) was performed, and two different age groups, adults and infants, were considered as populations at risk. The contribution of honey lay far below the acceptable daily intake (ADI) for both pesticide residues. Therefore, according to our results, honey is unlikely to pose concerns for consumer health in terms of its contribution to dietary long-term exposure. However, to maintain the level of compliance, pesticide residues in honey should be continuously monitored.